(untitled) (World Bulletin of Public Health, 2022)
The authors conducted a review of modern studies on the diagnosis of diseases of the gastrointestinal tract, non-invasive methods of examination of Helicobacter pylori associated gastrointestinal pathologies. The results of numerous studies by foreign and domestic authors are systematized.